Engineering and technology management tools and applications - Dhillon, B. S. (Balbir S.), 1947- (Artech House technology management and professional development library., 2002)
Career success for engineers who wish to move up the management ladder, requires more than an understanding of engineering and technological principles - it demands a profound understanding of today's business management issues and principles. In this unique book, the author provides you with a valuable understanding of contemporary management concepts and their applications in a technical organization. You get in-depth coverage of product selection and management, engineering design and product costing, concurrent engineering, value management, configuration management, risk management, reengineering strategies and benefits, managing creativity and innovation, information technology management, and software management. The large number of solved examples highlighted throughout the text underscore the value of this book as an indispensable "How To" manual, and library reference piece.